No words, just pictures to tell the history of humanity: an art case in Bocejo - Renata Junqueira de Souza; Flávia Brocchetto Ramos; Jeff Stevenson (Ilha do Desterro)
Wordless books are traditionally associated with illiterate children. However, many of them have fragmented and dense proposal, assuming skills and prior knowledge that a young reader would hardly have. Thus, in research whose focus is on books for children selected by the Brazilian – National Program of the School Library (PNBE), we chose to study Ilan Brenman and Renato Moriconi’s Bocejo. The book consists of apparent isolated scenes that, joined together, form a unique whole, dialoguing with stages that show the history of humanity – from bible’s Eve to the arrival of man on the moon or from the act of an individual reader to the interaction with the book. Lack of words that could guide the understanding of the reader, temporal gaps between scenes and the multiplicity of elements which compose each picture lead to structure and thematic fractures, that complicate the reception of the book by the beginning reader. The meanings of the story emerge by a picture and the articulation with the fact that the character represented is referring to. The proposal of the work prioritizes the emancipatory nature of the reader, however, in the case of young readers, mediation is necessary to help children in the process of comprehension, understanding the book and the art process involved in this humanity path.